The snowball : Warren Buffett and the business of life - Schroeder, Alice (New York : Bantam Books, 2008)
A portrait of the life and career of investment guru Warren Buffett sheds new light on the man, as well as on the work, ideas, business principles, strategies, and no-nonsense insights that have guided his phenomenally successful business endeavors.
Includes bibliographical references (p. [839]-928) and index.
Keywords: Buffett, Warren; Capitalists and financiers -- United States -- Biography; Investments -- United States